DISPUTE RESOLUTION OF JOINT PROPERTY AND INHERITED PROPERTY DUE TO DEATH DIVORCE BY MEDIATION - Awaludin, Ridwan; Muslimin, A; Mukhlishin, Ahmad; Hoggart, Fiona (SMART: Journal of Sharia, Traditon, and Modernity, 2022)
The problem of disputes over mutual assets or shared assets and inherited assets as a result of divorce and death is a matter that greatly affects the survival of the family left behind. This often leads to long conflicts. These conflicts sometimes cannot be resolved by the parties themselves, as was the case with one of the families in Tempuran Village, Trimurjo District. They resolve the conflict through mediation outside the court which of course presents a mediator as a neutral party. The formulation of the problem in this study is how to resolve disputes over shared assets and inherited assets in Tempuran Village, Trimurjo District? What is the method of mediation used to resolve joint and inherited property disputes between the wife's and stepfather's children in cases of divorce and death? This type of research is field research (Field Research), while the approach is qualitative with empirical laws that are anthropological social juridical. Data collection procedures were carried out through observation, interviews, and documentation. Primary data comes from interviews, while observation and documentation are secondary data that complements the primary data. The results of this study are that the distribution of joint assets (gono-gini) and inherited assets as a result of divorce is resolved through the kinship line. This family meeting is held to maintain family relations between stepfathers and stepchildren in harmony. The amount of the distribution of assets is in accordance with the agreement that has been mutually decided, namely the amount of distribution of assets back and forth and inherited assets for stepchildren is greater with a total of 2/3% of the existing assets. This is because the child's mother carries more assets than her stepfather.Keywords: Joint Assets, Inherited Assets, Divorced, Mediation Law.